LA MODELACIÓN Y CONSTRUCCIÓN DE NUEVAS FORMAS DE CONVIVENCIA SOCIAL - -CEO-, Centro de Estudios de Opinión (La Sociología en sus Escenarios, 2010)
Abstract. The modeling and construction of new forms of social coexistence. When considering the existence of a set of expressed social pathologies like violence, like crisis of values, political apathy, like unemployment, and others, the Council has thought about developing a program of rescue of the citizen opinion with the aim of recovering the citizen pulse like elements of real participation in the processes and conjunctures that the city lives, in such a way that shaking it brings back to consciousness individual is thought on the city in his different physical and social scales as they are the levels claypit, the neighborhood and the home. The proposed objective takes to think about the possibility of forging specific programs, arisen from the same opinion it publishes, and that could be incorporated to the Development plan of the City. Resumen. Al considerar la existencia de un conjunto de patologías sociales expresadas como violencia, como crisis de valores, como apatía política, como desempleo, y otras, la Consejería ha pensado en desarrollar un programa de rescate de la opinión ciudadana con el objetivo de recuperar el pulso ciudadano como elementos de participación real en los procesos y coyunturas que la ciudad vive, de tal manera que sacudiendo la conciencia individual se opine sobre la ciudad en sus diferentes escalas físicas y sociales como son los niveles barrial, el vecindario y el hogar.